2011
DOI: 10.1016/j.freeradbiomed.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of plasmalogens and their diacyl analogs with singlet oxygen in selected model systems

Abstract: Plasmalogens (Plg) are phospholipids containing vinyl ether linkage at the sn-1 position of the glycerophospholipid backbone. In spite of being quite abundant in humans, the biological role of plasmalogens remains speculative. It has been postulated that plasmalogens are physiological antioxidants with the vinyl ether functionality serving as sacrificial trap for free radicals and singlet oxygen. However, no quantitative data on the efficiency of plasmalogens to scavenge these reactive species are available. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 44 publications
4
85
1
1
Order By: Relevance
“…Due to the presence of a vinyl ether bond, plasmalogens are preferentially oxidized over diacylglycerophospholipids and the oxidative products of plasmalogens are unable to further propagate lipid peroxidation [41]. The small decrease in plasmalogens we observed in type 1 diabetic patients compared to controls did not reach statistical significance and our study suggests that plasmalogens are not responsible for the impaired anti-oxidative activity of HDL observed in type 1 diabetic patients [7].…”
Section: Discussioncontrasting
confidence: 66%
“…Due to the presence of a vinyl ether bond, plasmalogens are preferentially oxidized over diacylglycerophospholipids and the oxidative products of plasmalogens are unable to further propagate lipid peroxidation [41]. The small decrease in plasmalogens we observed in type 1 diabetic patients compared to controls did not reach statistical significance and our study suggests that plasmalogens are not responsible for the impaired anti-oxidative activity of HDL observed in type 1 diabetic patients [7].…”
Section: Discussioncontrasting
confidence: 66%
“…In a further study, oxidation of the plasmalogen vinyl-ether bond markedly prevented the oxidation of PUFAs (Engelmann, 2004). Broniec et al (2011) evaluated the efficiency of this process and showed that plasmalogens were able to protect unsaturated membrane lipids against oxidation by singlet oxygen without producing excessively toxic oxidation products. These data challenge a previous report on harmful effects of degradation products in inflammatory processes (Mankidy et al, 2010).…”
Section: Antioxidative Effectsmentioning
confidence: 98%
“…Therefore, ether GP may be seen as reservoirs for these biologically active lipid mediators, released upon PLA 2 hydrolysis. However, the most frequent role associated to ether GP is as an antioxidant, as it is generally accepted that the hydrogen atoms adjacent to the vinyl ether bond are preferentially oxidized over diacyl GP when exposed to various free radicals and singlet oxygen [10].…”
mentioning
confidence: 99%